All about derivatives - Durbin, Michael (New York : McGraw-Hill, 2011)
..."Derivatives provides a foundation on: The most common contracts available to you in today's market -- Key concepts such as cost of carry, settlement, valuation, and payoff -- Proven methods for establishing fair value -- How leverage can work for you--and against you -- The various derivative contracts traded today, including forwards, futures, swaps, and options -- Pricing methods and mathematics for determining fair value --Hedging strategies for managing and reducing different types of risk. Includes a brand-new chapter on the role derivatives played in the 2008 financial meltdown."--P. 4 of cover.
Derivatives in a nutshell -- The forward contract -- The futures contract -- The swap contract -- The option contract -- Credit derivatives -- Using derivatives to manage risk -- Pricing forwards and futures -- Pricing swaps -- Pricing options -- Hedging a derivatives position -- Derivatives and the 2008 financial meltdown.
Includes bibliographical references and index.
Keywords: Derivative securities; Swaps (Finance); Options (Finance); Securities